2016
DOI: 10.1038/jes.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for measuring residential socioeconomic factors associated with cardiovascular and metabolic health

Abstract: Individual-level characteristics, including socioeconomic status, have been associated with poor metabolic and cardiovascular health; however, residential area-level characteristics may also independently contribute to health status. In the current study, we used hierarchical clustering to aggregate 444 US Census block groups in Durham, Orange, and Wake Counties, NC, USA into six homogeneous clusters of similar characteristics based on 12 demographic factors. We assigned 2254 cardiac catheterization patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Measures of the food environment used in this study were based on highly curated data from the RECVD study (22). Although the main analytic approach we used in the present study used relative measures of the food environment, the Network also investigated absolute measures within the VADR cohort in a separate study, and results suggested that repeated sensitivity analyses with the other two samples were not indicated (38). Our choice to use relative availability as the primary food-environment measure for these analyses builds on prior research, including studies in which models with relative measures had better model fit than models with absolute measures (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Measures of the food environment used in this study were based on highly curated data from the RECVD study (22). Although the main analytic approach we used in the present study used relative measures of the food environment, the Network also investigated absolute measures within the VADR cohort in a separate study, and results suggested that repeated sensitivity analyses with the other two samples were not indicated (38). Our choice to use relative availability as the primary food-environment measure for these analyses builds on prior research, including studies in which models with relative measures had better model fit than models with absolute measures (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The values for the sensitivity analysis are shown in Table 3 and Table 4. The default values for the various model inputs and the high and low values were set to reasonable values observed in previously reported field studies [9,10,33] and epidemiological studies [11,34] in central NC. The default values for Q fan and CADR were set to the application default values.…”
Section: Methodsmentioning
confidence: 99%
“…Homeownership historically represents higher levels of SES; it is directly associated with wealth accumulation, community building, neighborhood stability, and overall economic well-being [ 20 , 21 ]. In contrast, lower neighborhood-level SES is associated with increased psychosocial stress, fewer environmental amenities, and decreased access to parks, high-speed internet, libraries, and other local infrastructure [ 14 , 22 ]. These resources allow people to address potential health risks, and people without access tend to have poorer health [ 17 ].…”
Section: Introductionmentioning
confidence: 99%